Iron, hepcidin, and microcytosis in canine hepatocellular carcinoma. (10th March 2022) - Polak, Klaudia Z.; Schaffer, Paula; Donaghy, Dillon; Zenk, Madison C.; Olver, Christine S.
Abstract: Background: Erythrocyte microcytosis in some dogs with hepatocellular carcinoma (HCC) suggests a derangement in systemic iron. Hepcidin, the master regulator of iron, is secreted by the liver in response to interleukin 6 (IL‐6) and/or bone morphogenetic protein 6 (BMP6) and can cause microcytosis. Objectives: Pilot study to compare the quantities of hepcidin, IL‐6, and BMP6 RNA molecules in archival tumoral (HCC) and adjacent peritumoral (non‐HCC) hepatic tissue to determine if they are different between tissue types or associated with microcytosis. Methods: RNA was isolated from formalin‐fixed, paraffin‐embedded HCC and non‐HCC tissue from seven microcytic dogs and four normocytic dogs. Digital RNA counts of hepcidin, IL‐6, or BMP6, and six other iron‐regulatory genes were determined using the Nanostring nCounter system. The area of blue on each section was digitally evaluated to measure the extent of Prussian blue staining objectively. Parameters were compared between HCC and non‐HCC tissue and between microcytic and normocytic groups. Results: Hepcidin was decreased, and transferrin receptor 1 (TfR1) was increased in HCC tissue compared with non‐HCC tissue. Non‐HCC hepcidin RNA counts correlated negatively with MCV and positively with the extent of iron staining. Hepcidin expression was higher in non‐HCC tissue of microcytic cases than in normocytic cases. Conclusions: Canine HCC cases showed relatively increased iron staining in non‐HCC tissue and decreased hepcidin RNA in HCC tissue. Microcytic cases had higher hepcidin RNA in non‐HCC tissue than normocytic cases. Future studies may extend these findings to protein quantification, cellular localization of RNA changes, and determining if iron loading in canine liver is a predisposing factor for HCC.